Ashes on the waves - Lindsey, Mary, 1963- (Philomel Books, 2013)
Expands on the Edgar Allan Poe poem, Annabel Lee, as Liam and Anna reunite on an isolated Maine island where they were children together and fall so deeply in love they provoke a wager between Otherworld creatures from Celtic mythology.